Implementasi Kegiatan Kokulikuler “ Menari “ untuk Melatih Keterampilan Psikomotorik Kasar pada Peserta Didik di Madrasah Ibtidaiyah Asy-Syifa Kota Bengkulu - Sari, Lara; Malau, Maria Dina Mariana; Ilahi, Repaldo Rahmat; Legiana, Syafira; Nurhalimah, Ullik; Zubaidah, Zubaidah (Faculty of teaching training and education, 2024)
Dancing co-curricular activities are activities that are usually carried out in the morning before noon, starting at 09.00 AM until 09.30 AM. After that, this researcher showed that the habituation of co-curricular activities carried out by students was routine, alternately 4 days a week for 30 minutes, and carried out by male and female students. The focus in this research is 1). What is the purpose of implementing dancing co-curricular activities for MI Asy-Syifa students? 2). How does it apply to MI Asy-Syifa students? 3). What is the effect on gross psychomotor development in students at MI Asy-Syifa? The objectives of this research are, 1). To find out the purpose of carrying out dancing co-curricular activities for MI Asy-Syifa students. 2). To find out how it applies to students at MI Asy-Syifa. 3). To find out what effect dancing co-curricular activities have on gross psychomotor development in MI Asy-Syifa students. This type of research uses a qualitative approach using data source methods obtained from three types of data sources, namely, data collection techniques in the form of observation, interviews, documentation.